2006
DOI: 10.1007/s10681-006-0446-0
|View full text |Cite
|
Sign up to set email alerts
|

Farmer participatory evaluation confirms higher grain yields in spring wheat using a selection index for spot blotch resistance, maturity and kernel weight

Abstract: Wheat (Triticum aestivum L.) cultivars for the warm regions of South Asia must produce high yields and possess resistance to spot blotch (Cochliobolus sativus), early maturity and high kernel weight. A study was conducted to determine the effectiveness of selecting for high grain yield based on a selection index for spot blotch resistance, maturity and kernel weight in four wheat crosses involving a susceptible cultivar and resistant genotypes. Initial selection of 40 progeny lines in each cross had been made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…being more promising. This approach was shown to be effective in the selection process to identify improved progenies (Sharma and Duveiller, 2003, 2006a). In many locations, screening for spot blotch in the field is based on natural infection at hot‐spot locations such as Bhairhawa and Rampur (Nepal), the Varanasi area in Uttar Pradesh (India) and the lowlands of Poza Rica (Veracruz) in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…being more promising. This approach was shown to be effective in the selection process to identify improved progenies (Sharma and Duveiller, 2003, 2006a). In many locations, screening for spot blotch in the field is based on natural infection at hot‐spot locations such as Bhairhawa and Rampur (Nepal), the Varanasi area in Uttar Pradesh (India) and the lowlands of Poza Rica (Veracruz) in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that PPB provided more information than non‐PPB at the same cost. Sharma and Duveiller (2006) reported that wheat variety selection based on the farmers’ preference criteria for desirable genotypes was effective in identifying varieties with superior agronomic performance and spot blotch disease resistance. In another successful case, Danial et al.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that PPB provided more information than non-PPB at the same cost. Sharma and Duveiller (2006) reported that wheat variety selection based on the farmers' preference criteria for desirable genotypes was effective in identifying varieties with superior agronomic performance and spot blotch disease resistance. In another successful case, Danial et al (2007) reported that breeders learnt about male and female farmers' selection criteria of preferred varieties and used the knowledge in the selection and development of new wheat, barley, common bean, quinoa, potato and maize cultivars in the Andean region.…”
Section: Introductionmentioning
confidence: 99%
“…However, green revolution has not improved wheat production in marginal areas of the world having resource poor farmers (Sthapit et al, 1996). In order to address the problems of resource poor farmers, farmer participatory approaches were advocated by many workers (Farrington and Martin, 1988;Sthapit et al, 1994;Josi and Witcombe, 1996; Witcombe, 1996;Witcombe et al, 2003;Weltzien et al, 2003;Ashby and Lilja, 2004;Morris and Bellon, 2004;Ceccarelli and Grando, 2005;Mangione et al, 2006;Sharma and Duveiller, 2006) in selection and breeding programs. In centralized breeding system, a number of advanced breeding lines are tested and selected under research station conditions that may not resemble the environmental conditions where the lines will be subsequently grown.…”
Section: Discussionmentioning
confidence: 99%